2020
DOI: 10.1186/s41232-020-00142-7
|View full text |Cite
|
Sign up to set email alerts
|

Glioma progression and recurrence involving maintenance and expansion strategies of glioma stem cells by organizing self-advantageous niche microenvironments

Abstract: Due to the nature of enhanced resistance to conventional chemo/radiotherapies and metastasis, highly tumorigenic cancer stem cells (CSCs) have been proposed as a promising target for cancer eradication. To tackle the therapeutic difficulties of cancers involving CSCs, extensive research efforts have been directed toward understanding the extracellular microenvironments of CSCs, i.e., CSC niche, which plays important roles in CSC maintenance and expansion. Here we review recently identified mechanisms of mainte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Both pathways are related to tumorassociated immune cells and regulate immunotherapeutic responses (72). Taga et al reported that co-expression of genes related to the extracellular matrix, iron metabolism, and macrophages was associated with treatment outcomes in patients with glioma (36). mTOR complex 2 can control iron metabolism by regulating acetylation of iron-related genes promoter, promoting tumor cell survival (73).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both pathways are related to tumorassociated immune cells and regulate immunotherapeutic responses (72). Taga et al reported that co-expression of genes related to the extracellular matrix, iron metabolism, and macrophages was associated with treatment outcomes in patients with glioma (36). mTOR complex 2 can control iron metabolism by regulating acetylation of iron-related genes promoter, promoting tumor cell survival (73).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, recurrence or malignant progression is still inevitable, even after treatment with surgical resection, radiotherapy, chemotherapy and immunotherapy. Recently, iron metabolism was found to participate in glioma tumorigenesis, progression, and the tumor microenvironment ( 14 , 36 ). GBM cancer stem-like cells uptake much more iron than non stem-like cells ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of GSCs emerged in the early 2000s but remained to be fully characterized ( Hemmati et al, 2003 ; Singh et al, 2003 ; Galli et al, 2004 ). As a subpopulation of tumor cells, GSCs are the driving force of tumor recurrence and can self-renew and differentiate ( Taga and Tabu, 2020 ). Unlike GSCs, NSCs are tumor-tropic cells that can be used as vehicles to selectively deliver various anticancer agents to tumor sites ( Mooney et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several groups isolate and characterize stem-like cancer cells in glioma [6][7][8], which lead to the realization that GSCs are resistant to chemotherapy and radiotherapy [9,10]. Some groups try to find the genes which regulate GSCs maintenance and glioma progression [11][12][13][14][15][16][17]. Inspite of so many struggles, the prognosis of GBM has not enhanced in the past decade [17].…”
Section: Introductionmentioning
confidence: 99%